Revisiting the Trends of Female Labour Force Participation in Indonesia - Utomo, Ariane (Yayasan Jurnal Perempuan, 2018)
There are two problems that often emerge in public discussions about the recent trends in the level of participation of the female labor force in Indonesia. The first is the low Indonesian female labour force partipation rate (FLFPR) compared to other ASEAN countries. The second is the trend of stagnation of Indonesian FLFPR—at around 51%—over almost three decades. By reviewing cross-country data from the Global Gender Gap Index and the International Labor Organization, this article rests on the argument that the two features of Indonesian FLFPR are not merely bad news, and should be read in the context of large economic growth and social change in Indonesia. But a more critical and thorough interpretation of the trend of this indicator does not deny the fact that there is still wide room to improve women's economic participation and opportunity in Indonesia.